Sodium Alginate–Starch Capsules for Enhanced Stability of Metformin in Simulated Gastrointestinal Fluids - Roxana Gheorghita; Ioan-Ovidiu Sirbu; Andrei Lobiuc; Mihai Covasa (Biomimetics)
The use of biopolymers in pharmaceuticals is well established, particularly for encapsulating biologically active compounds due to their beneficial properties. Alginate, widely recognized for its excellent encapsulation abilities, is the most commonly used biopolymer, while starch, typically known as insoluble dietary fiber, also serves as an effective agent for trapping and protecting compounds during processing, storage, and gastrointestinal transit. Sodium alginate–starch capsules with varying compositions were analyzed to develop metformin hydrochloride (MET) containing capsules with adequate physicochemical properties. In vitro testing with simulated gastrointestinal fluids showed that after 1 h, capsules with equal amounts of alginate and starch had a higher swelling ratio and better drug release behavior, despite lower MET entrapment efficiency compared to other formulations. Microstructural analysis revealed stability in simulated gastric fluids and solubility in simulated intestinal fluids, key factors in drug development. The results suggest that these biopolymeric compositions are highly resistant to gastric fluids and minimally soluble in the intestines, making them suitable for extended drug release. This research evaluates key technological parameters of a cost-effective encapsulation method for the controlled release of active substances, providing a versatile solution for pharmaceutical and biomedical applications.